Emotion in Bipolar I Disorder: Implications for Functional and Symptom Outcomes - Johnson, Sheri L. (J Abnorm Psychol, 2015)
Despite the centrality of emotion disturbance in neurobiological models of bipolar disorder, the behavioral literature has not yet clearly identified the most central aspects of emotion disturbance in bipolar disorder. Toward this aim, we gathered a battery of emotion-related measures in 67 persons diagnosed with bipolar I disorder as assessed with SCID and a well-matched control group of 58 persons without a history of mood disorders. Those with bipolar disorder were interviewed monthly until they achieved remission, and then tested on emotion measures. A subset of 36 participants with bipolar disorder completed symptom severity interviews at 12-month follow-up. Factor analyses indicated four emotion factor scores: Negative Emotion, Positive Emotion, Reappraisal and Suppression. Bivariate analyses suggested that bipolar disorder was tied to a host of emotion disturbances, but multivariate analyses suggested that bipolar disorder was particularly tied to elevations of Negative Emotion. High Negative Emotion, low Positive Emotion, and high Suppression were conjointly related to lower functioning. Reappraisal predicted declines in depression over time for those with bipolar disorder. Findings highlight the importance of considering the overall profile of emotion disturbance in bipolar disorder. Emotion and emotion regulation appear central to a broad range of outcomes in bipolar disorder.